Goal Congruence Dalam Pengelolaan Restoran Padang - Hanif Hanif (Journal of Economic, Bussines and Accounting (COSTING), 2022)
The balance of the organization or company in the long term is determined by the level of alignment of goals (goal congruence) of the parties who run the company. Broadly speaking, the parties in the company are grouped into two, namely the founders or owners of the company and the employees who run the company, starting from the directors and the ranks and workers. The goals of the company, which also reflect the goals of the owners and founders of the company, are not necessarily the same as those of the directors and the ranks and the workers. A conflict of interest is very likely to occur between them because naturally indeed the goals of both parties can be opposites. The purpose of writing this paper is to present the results of research in the Sederhana Restaurant group, which forms a concept of company management supported by profit sharing accounting based on mato system (hereinafter abbreviated as mato system) which can increase goal congruence among stakeholders in the company. The research uses a case study approach to understand the reality of goal congruence. Researchers visited the field, held discussions with the founders of the company, the board of directors, branch leaders, and employees. The Sederhana Restaurant (Sa) Jakarta research site, which is focused on one of the main branches in Rawamangun. The results of the interview were analyzed and resulted in the conclusion that the mato system is able to bridge and align the goals of the founders of the company with the Directors, Branch Leaders, and their workers so as to encourage a high level of goal congruence. Keywords: conflict of interest. Goal congruence, case studies, mato system.